Palladium-Catalyzed Regioselective C-5 Arylation of 1,2,3-Triazoles with Diaryliodonium Salts - Gang, Fangli; Che, Yang; Du, Zhengyin; Feng, Hua; Fu, Ying (Synlett, 2017)
An effective method for C-5 arylation of 1,4-disubstituted 1,2,3-triazoles and C-5 regioselective arylation of 1-substituted 1,2,3-triazoles via sp2 C–H activation with palladium as a catalyst and diaryliodonium salts as arylating reagents is described. Various electron-rich and electron-deficient substituents attached to triazoles and diaryliodonium salts were tolerable to give the desired products with good isolated yields in 24 hours under air atmosphere.
Keywords: arylation; diaryliodonium salts; regioselectivity; 1,2,3-triazoles; C–H activation